Pengaruh Pemberian Pupuk Organik Kotoran Sapi dan Mulsa Plastik Terhadap Pertumbuhan dan Hasil Cabai Rawit (Capsium frutescens L.) - Muhammad Kasim; Moresi M. Airtur; Peters O. Bako (Wana Lestari, 2024)
This research was carried out from March to July 2023 in the Fatukoa-Maulafa sub-district of Kupang, with the aim of determining the response to growth and yield of cayenne pepper plants (Capsium frutescens L.) due to the influence of doses of cow dung manure and the application of plastic mulch. This research is a factorial research using a Randomized Group Design (RAK). The factors tested consisted of the plastic mulch factor (M) with 2 levels, namely without mulching (m0) and black plastic mulch (m1) and the dose of cow dung organic fertilizer factor (K) consisting of 4 levels, namely without giving a fertilizer dose. cow manure (k0), cow manure organic fertilizer dose 10 tons ha-1, cow manure organic fertilizer dose 20 tons ha-1, and cow manure organic fertilizer dose 30 tons ha-1, so there are 8 treatment combinations. Each treatment combination was repeated 3 times. The data obtained was analyzed using variance analysis, and if the results of variance analysis showed a real effect, a test was carried out using the advanced Duncan Multiple Range Test (DMRT) at 5% level. The results of this study indicate that the interaction of the dose of cow dung manure with plastic mulch has a significant effect on the average LAB, average LTR, and weight of cayenne pepper fruit per plant, but the interaction has no significant effect on plant height, number of productive branches, and number of chili fruit per plant.